Ethno-veterinary practice for the treatment of cattle diseases in the eastern highlands of Nigeria - Nodza, George Isaac; Onuminya, Temitope; Igbari, Aramide Dolapo; Ogundipe, Temitayo Oluwatoyin; Abdulhameed, Ahmad (Ethnobotany Research and Applications, 2022)
Background: Cattle rearing is the main means of livelihood for the Fulani people in the highlands of Gashaka Gumti National Park in Nigeria, however the remote location and inaccessible terrain prevent access to modern veterinary care. This puts both livestock and their keepers at risk. To survive, the inhabitants of this area rely on traditional methods to heal their animals. Regrettably, the Ethno-veterinary Medicine (EVM) knowledge in this region is jeopardized by the locals changing their preferences due to rapid socio-economic, environmental and technological changes taking place all over the world. Therefore, documenting the therapeutic knowledge of the medicinal plant is imperative to prevent it from being lost. Materials and Methods: We conducted repeated field surveys and data were collected from sixty community members using semi-structured questionnaires through participatory rural appraisal (PRA) and rapid rural appraisal (RRA) approach. Results: A total of eighty-eight (88) plant species belonging to 73 genera and 37 families, were recorded for the treatment of 24 cattle diseases. The most represented families were Fabaceae (17 species), and Asteraceae (7 species). Trees were the dominant plants recorded (49 species). Pterocarpus erinaceous was the most widely used therapeutic plant species. Leaves (27%) were the most widely used plant parts, followed by the whole plant (22%), stem bark (14%), and others. The most frequent route of medicinal administration was oral, followed by topical application. Out of the 24 ailments recorded, Bovine tuberculosis was the most reported ailments followed by Pneumonia. Conclusion: Together, these data show that the Fulani people in the study area have a vast knowledge of medicinal plants useful for effective treatment of cattle illness where traditional veterinary care is unavailable. It is pertinent to say that our study has made an important contribution towards the preservation of EVM knowledge of the study area. Therefore, subjecting the most utilized species to a phytochemical and pharmacological investigation is imperative for possible novel discovery and the production of cheap drugs. Keywords: Gashaka Gumti National Park, Chabbal Hendu, Afromontane, Fulani, Tuberculosis